1996
DOI: 10.1088/0268-1242/11/10/016
|View full text |Cite
|
Sign up to set email alerts
|

Optical property simulation of single-layer halftone phaseshifting masks for DUV microlithography

Abstract: An optical simulation for a single-layer halftone phaseshifting mask (SLHTPSM) has been established and verified by the experimental data from several different sources. This simulation is suitable for a wide lithography exposure wavelength; for example, i-line, KrF and ArF etc. Theoretical analyses give some important tendencies of the optical parameters such as refractive index, extinction coefficient and film thickness. The optimum SLHTPSM structures for KrF (248 nm) have been derived by the simulation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…( 1) was used to improve the contrast by setting the phase difference between the absorption region and the reflection region at 180°. 18) λ is the wavelength of EUV light, θ is the angle of incidence, and n 1 and n 2 , d 1 and d 2 are the refractive coefficients and thicknesses of thin films 1 and 2, respectively. However, an additional 0.2 π phase shift may be required to compensate for the phase difference caused by the mask 3D effect.…”
Section: Imaging Performance By the Absorbermentioning
confidence: 99%
See 1 more Smart Citation
“…( 1) was used to improve the contrast by setting the phase difference between the absorption region and the reflection region at 180°. 18) λ is the wavelength of EUV light, θ is the angle of incidence, and n 1 and n 2 , d 1 and d 2 are the refractive coefficients and thicknesses of thin films 1 and 2, respectively. However, an additional 0.2 π phase shift may be required to compensate for the phase difference caused by the mask 3D effect.…”
Section: Imaging Performance By the Absorbermentioning
confidence: 99%
“…A recent study reported by van Lare et al showed that for EUV imaging, a 1.2 π phase shift is crucial for good performance. 19,20) The effect of the PSM can be maximized when the thickness of the phase shift layer, refractive index, and extinction coefficient are matched to the wavelength of light 18) p l q…”
Section: Imaging Performance By the Absorbermentioning
confidence: 99%